PUSAT MODIFIKASI OTOMOTIF KOTA PONTIANAK - Raka Maulana; Bontor Jumaylinda BR Gultom; Emilya Kalsum (JMARS: Jurnal Mosaik Arsitektur, 2022)
Understanding automotive is a science that reviews various types of transportation that use machines as a source of propulsion. Modifications generally change, add, and repair certain parts that aim to improve quality, features and style. A modification center was built to provide space for creativity or hobbies for communities, organizations and individuals. The modification center must also pay attention to the things needed by the modifiers, especially customers/immigrants. The condition of the modification workshops in Pontianak City are generally only found in homes that do not meet the standards in designing modification workshops in general so that the services are not necessarily good, such as exhibition rooms, workshop activity rooms, management rooms, and service rooms in handling waste. Various automotive that can be modified such as cars, motorcycles, and others. Where they want to update or add the desired variations. West Kalimantan, especially Pontianak, holds many events for car and motorcycle modification contests. The event is usually held at Rumah Radakng and Qubu Resort by collecting, presenting, compiling and analyzing data in order to obtain an approach to planning and design programs to be further used for program preparation and basic concepts of planning and design of modification workshop.